Functional group identification of Mimosa Pudica by UV-Visible and FT-IR spectroscopy - K. Viswanathan; Karthik Kannan; S. Christopher Jeyaseelan; Gurushankar, K. (Journal of Bio-Molecule Research and Engineering, 2022)
Medicinal plant research involves much more than drug discovery. This area has been expanded to include various topics, such as power negotiations based on medicinal plant lore. A wide range of modern medicines is derived directly or indirectly from plants. Some of these drugs are no longer synthesized in significant quantities by competitors because they have been toxic to humans and other animals. Therefore, this study focuses on scientific research to confirm the knowledge of the phytocompounds of Mimosa pudica by UV-Visible and FT-IR spectroscopy. It also provides clues for evaluating its performance in various fields.